2022
DOI: 10.1097/pgp.0000000000000849
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Tumor Resembling Ovarian Sex Cord Tumor With Aggressive Histologic Features Harboring a GREB1-NCOA2 Fusion: Case Report With a Brief Review

Abstract: Uterine tumor resembling ovarian sex cord tumor (UTROSCT) is a rare mesenchymal neoplasm, of uncertain lineage, that shows predominantly sex cord-like differentiation with a broad range of histologic appearances and polyphenotypic immunohistochemical features. Although generally having a favorable prognosis, a subset can recur/metastasize. Most recently, several studies of UTROSCT have described novel fusion genes involving ESR1 and GREB1 as the 5 partner, and NCOA1-3 as the 3 partner. Genotype and phenotype c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
4
1
Order By: Relevance
“…The mean tumor size was 5.4 cm, 1–15 which is quite similar to the 2 largest series (6.1 cm and 5.1 cm, respectively). As the largest cohort to date, the age of 7 GREB1::NCOA2 patients in our study was younger than 5 previously reported patients 7,8,11,13,40 (33 y–56 y, mean 48 y vs. 51 y–74 y, mean 60 y, P =0.049). Five GREB1 :: NCOA1 patients were significantly younger than the 6 reported cases (50 y vs. 68 y, P =0.001) 8,11,41 .…”
Section: Discussioncontrasting
confidence: 49%
“…The mean tumor size was 5.4 cm, 1–15 which is quite similar to the 2 largest series (6.1 cm and 5.1 cm, respectively). As the largest cohort to date, the age of 7 GREB1::NCOA2 patients in our study was younger than 5 previously reported patients 7,8,11,13,40 (33 y–56 y, mean 48 y vs. 51 y–74 y, mean 60 y, P =0.049). Five GREB1 :: NCOA1 patients were significantly younger than the 6 reported cases (50 y vs. 68 y, P =0.001) 8,11,41 .…”
Section: Discussioncontrasting
confidence: 49%
“…We assume that the future of UTROSCT diagnosis and treatment-including the decision to preserve the uterus or not-will be the molecular-genetic testing, as it has become common in other gynecologic malignancies, e.g., endometrial carcinoma [148,149]. This hypothesis is supported by numerous recent studies [86,105,109,[123][124][125][126][128][129][130][131][132] that identified factors associated with aggressive clinical behavior and recurrence. In UTROSCT, GREB1 or ESR1 often fuse with members of the p160 steroid receptor coactivator family, which includes NCOA1, NCOA2, and NCOA3.…”
Section: Discussionmentioning
confidence: 93%
“…Regarding prognosis, GREB1-rearranged tumors tended to occur in significantly older women than UTROSCT with ESR1 fusions; moreover, GREB1-rearranged tumors tended to be larger and more mitotically active and behave more aggressively [105]. Recently, Yin et al [86] described novel fusion genes involving ESR1 and GREB1 as the 5 ′ partner and NCOA1-3 as the 3 ′ partner. Genotype and phenotype correlation has suggested that GREB1-rearranged UTROSCTs may have a higher tendency to behave aggressively.…”
Section: Risk Factors and Prognostic Factorsmentioning
confidence: 99%
“…More recently, some molecular biology studies have revealed that UTROSCTs with GREB1::NCOA1-3 fusions [51,58] and PD-L1 molecule expression appear to be predisposed to more aggressive behavior and recurrences, GREB1::NCOA2 being the most common gene fusion in recurrent tumors [61]. As well as, recently Yin et al observed a case of UTROSC with aggressive histologic features harboring a GREB1-NCOA2 fusion, such as increased mitotic figures (up to 3/10 high power fields), geographic necrosis, and LVI [99].…”
Section: Discussionmentioning
confidence: 99%